Co-expression of mFat-1 and pig IGF-1 genes by recombinant plasmids in modified chitosan nanoparticles and its synergistic effect on mouse immunity. Issue 1 (December 2017) - Xiong, Qi; Chen, Jianlin; Li, Fei-Lin; Zhao, Shiji; Wan, Xiaoping; Yang, Xiao; Li, Jianglin; Luo, Danyu; Wang, Zezhou; Lv, Xuebin; Gao, Rong
Abstract To develop a cost-effective molecular regulator to improve growth metabolism and immunity of animals, a recombinant plasmid co-expressing fatty acid desaturase (mFat-1) and pig insulin growth like factor 1 (IGF-1) genes was constructed by the 2 A self-cleavage technique. After entrapment within modified chitosan nanoparticles (chitosan modified with polyethyleneglycol–polyethylenimine, CPP), the recombinant plasmid was injected intramuscularly into mice. Compared with controls, co-expression of mFat-1 and IGF-1 significantly raised the level of serum IGF-1, and increased the liver and muscle docosa hexaenoic acid (DHA) content. Th and Tc cell levels were also elevated, as were expression levels of serum IL-4 and IL-6 genes. These results demonstrate that the immunity and metabolism of an animal can be effectively improved by co-expression of mFat-1 and IGF-1 genesin vivo, which may contribute to further development of novel immunomodulators with beneficial effects on growth metabolism and immunity.